Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Integral Transform: F DX X F X K

Download as pdf or txt
Download as pdf or txt
You are on page 1of 8

Chapter 2

Integral Transform
2.1 Introduction

Consider pairs of functions related by an expression of the form:

b
F (α) = ∫ K (α , x ) f ( x ) dx

(2.1-1)
a

The function F (α) is called the integral transform of f(x) by the kernel K(α, x). The

operation may also be considered as mapping a function f(x) in x-space into another function
F (α) in α-space. Figure 2.1-1 depicts the idea behind the application of integral transform.

Certain problems can be solved, if at all, in the original coordinates (space). These problems
might be solved relatively easily in the transform coordinates. Then, the inverse transform
returns the solution from the transform coordinates to the original system.

Problem in Relative easy solution Solution in


transform space transform space

Integral Inverse
transform transform

Original Difficult solution Solution of


problem original problem

Figure 2.1-1 Application of integral transform.

Two of the most useful of the infinite number of possible transforms are the Laplace
transform,


∫ e − sx f ( x ) dx

F (s) = (2.1-2)
0

and the Fourier transform,


∫ e −ikx f ( x ) dx

F (k) = (2.1-3)
−∞

Integral transform can be used to reduce the number of independent variables in a partial
differential equation by one. Thus, the one-dimensional heat equation or wave equation can
be transformed into an ordinary differential equation in the transformed function F (α). An

ordinary differential equation becomes an algebraic equation in the transformed domain. It is
usually easier to solve the resultant equation in the transform space than it is to solve the
original equation.

2-1
2.2 The Laplace Transform

Laplace transform is usually used to analyze process dynamic and to design control system.
Therefore one of the independent variables is time. The Laplace transform of a function f(t) is
defined by


∫ e − st f (t ) dt

L{f(t)} = F (s) = (2.2-1)
0

In this equation s is a parameter that may be complex. However we will mostly consider
system with real value of s. For the Laplace transform to exist (or the integral (2.2-1) to have
a finite value), s must be greater than zero if s is real, or the real part of s must be greater than
zero if s is complex. The Laplace transform therefore converts a function of t into a function
of s. The limits of integration show that the Laplace transform contains information on the
function f(t) for positive time only. This is perfectly acceptable for a physical system since
nothing can be done about the past (negative time). Some examples of Laplace transform


L{t2} = F (s) = ∫ e − st t 2 dt

0


e − st 2 ∞
L{t } = − t ∫ e − st tdt
2 2
+
s 0
s 0

∞ ∞
2  e − st 1 ∞  2 e − st
L{t } = 0 + − t
2
+ ∫ e − st dt  = − 2
s s s 0  s s
 0 0

2
L{ t 2 } =
s3

n!
In general L{tn} = , where n is an integer.
s n +1

∞ ∞ 1
L{eat} = ∫ e − st e at dt = ∫ e −( s −a ) t dt =
0 0 s−a

The Matlab command Laplace will take the Laplace transform of a function f(t)

>> syms s t a
>> laplace(t^2)
ans =
2/s^3
>> laplace(exp(a*t))
ans =
1/(s-a)

2-2
Example 2.2-1 ----------------------------------------------------------------------------------

Determine the Laplace transform of sin ωt

Solution ------------------------------------------------------------------------------------------

The sine wave is represented in exponential form by

e iωt − e − iωt
sin ωt =
2i

e iωt − e − iωt at
∫ [e ]
∞ 1 ∞
L{sin ωt} = ∫ e dt = −( s −iω ) t
− e −( s +iω ) t dt
0 2i 2i 0


1  e −( s −iω ) t e −( s +iω ) t  1  0 −1 0 −1 
L{sin ωt} = − s − iω + s + iω  = 2i − s − iω + s + iω 
2i  0

1 2iω ω
L{sin ωt} = = 2
2i s + ω
2 2
s +ω2

Matlab can also take the Laplace transform of sine function.

>> syms s t a w
>> laplace(sin(w*t))
ans =
w/(s^2+w^2)
---------------------------------------------------------------------------------------------------------

For the integral ∫ e − st f (t ) dt to exit f(t) should be of exponential order as t → ∞ or, in
0
another word, cannot grow faster than an exponent. We say that f(t) is of exponential order if
there exists a constant α such that

lim
e −αt f (t ) = finite
t→∞

For example, the functions 1, 4cos 2t, 5tsin 2t, tn are all of exponential order because f(t)e-bt
→ 0 as t → ∞ for any b > 0. Function exp(t2) is not of exponential order since it diverges
much faster than ebt for any value of b.

The above conditions for the Laplace transform to exist are sufficient, but not necessary. The
function t-1/2 is not of exponential order, because the function is infinite at t = 0. However its
Laplace transform exits for all s >0. In this case

2-3
π 
1/ 2

− st −1 / 2

-1/2 ⌢
L{ t } = F (s) = e t dt =  
0
s

2.3 Properties of The Laplace Transform


Linearity

The Laplace transform is a linear operation. This means that if a is a constant, then

L{af(t)} = aL{f(t)} = a F (s) (2.3-1)

The distributive property of addition also follows from the linearity property:

L{af(t) + bg(t)} = a F (s) + b Ĝ (s) (2.3-2)

These properties can be derived form the definition of Laplace transform.

First Translation Property

If L{f(t)} = F (s) then L{eatf(t)} = F (s - a)


⌢ ⌢
s>a (2.3-3)

This property is useful for evaluating transforms of functions that involve exponential
functions of time.

Second Translation Property

This property deals with the translation of a function in the time axis, as shown in Figure 2.3-
1.

f ( t)
f ( t-2 )
1

0 .8

0 .6
f(t) and f(t-a)

0 .4

0 .2

0 1 2 3 4 5 6 7 8 9 10
t

Figure 2.3-1 Function delayed in 2 unit of time.

2-4
The translated function is the original function delayed in time as function defined by

 0 0≤t<a
g (t ) =  (2.3-4)
 f (t − a ) a≤t

In this equation g(t) is simply f(t) shifted a units to the right as shown in Figure 2.3-1. The
second translation property is given as

L{f(t − a)} = e-as F (s)



(2.3-5)

This property can be proved as follow


L{f(t − a)} = ∫ e − st f (t − a ) dt
0

Let τ = t − a (or t = τ + a), the above equation becomes

∞ ∞
L{f(t − a)} = ∫ e − s (τ + a ) f (τ )dτ = ∫ e − sτ e −as f (τ )dτ
−a 0


L{f(t − a)} = e −as ∫ e − sτ f (τ )dτ = e-as F (s)

0

g(t) can be written in term of f(t − a) with the use of unit step function U(t) defined by

0 t < 0
U (t ) = 
1 0 < t

With this definition g(t) = U(t − a)f(t − a), and equation (2.3-5) can be written as

L{U(t − a)f(t − a)} = e-as F (s)



(2.3-6)

Example 2.3-11. ----------------------------------------------------------------------------------

Find the Laplace transform of e-2tcos ωt

Solution ------------------------------------------------------------------------------------------

∞ s
We have L{cos ωt} = ∫ e − st cos ωtdt =
0 s +ω2
2

1
McQuarrie, D.A., Mathematical Methods for Scientists and Engineers, University Science Book, 2003, pg.
813

2-5
Replacing s by s + 2 gives

s+2
L{e-2tcos ωt} =
( s + 2) 2 + ω 2

Example 2.3-22. ----------------------------------------------------------------------------------

Plot the function defined by f(t) = 3 − 4(t − 1)U(t − 1) + 4(t − 3)U(t − 3)

Solution ------------------------------------------------------------------------------------------

The function can be expressed as

 3 0 ≤ t <1

f(t) =  3 − 4(t − 1) = 7 − 4t 1≤ t < 3
3 − 4(t − 1) + 4(t − 3) = −5 3≤t

and is plotted in Figure E2.3-2


f(t)
3

1 3 t

-5

Figure E2.3-2 Plot of f(t) = 3 − 4(t − 1)U(t − 1) + 4(t − 3)U(t − 3)


--------------------------------------------------------------------------------------------------

Differentiation Property

This property, which establishes a relationship between the Laplace transform of a function
and that of its derivatives, is used to transform ordinary differential equations into algebraic
equations.

 df (t )  ∞ df (t ) − st
∫ e dt = s F (s) − f(0)

L  = (2.3-7)
 dt  0 dt

This property can be obtained from the definition of Laplace transform as follows

Integrate by parts

2
McQuarrie, D.A., Mathematical Methods for Scientists and Engineers, University Science Book, 2003, pg.
814

2-6
u = e-st ⇒ du = − se-st

df (t )
dv = dt ⇒ v = f(t)
dt

 df (t )  ∞ ∞ ∞
L  = e f (t ) 0 −
-st
∫ f ( t )( − se − st )dt = − f(0) + s ∫ f ( t )e − st dt
 dt  0 0

 df (t ) 
 = s F (s) − f(0)

L
 dt 

The differentiation property can be extended to higher derivatives

 d n f (t )  n-2 df ( t ) d n −1 f (t )
 = s F (s) − s f(0) − s − ... −
n ⌢ n-1
L (2.3-8)
 dt 
n
dt t =0 dt n −1 t =0

Integration Property

This property establishes the relationship between the Laplace transform of a function and
that of its integral.

L {∫ f (t)dt} = 1s F⌢ (s)
0
t
(2.3-9)

Final Value Property

This property can be used to find the final, or steady-state, value of a function from its
transform. It is also useful in checking the validity of derived transforms. If the limit of f(t) as
t → ∞ exits, then it can be found from its Laplace transform as follows:

lim f (t ) lim sFˆ ( s )


= (2.3-10)
t→∞ s→0

Example 2.3-33. ----------------------------------------------------------------------------------

Derive the Laplace transform of the differential equation

d 2 y (t ) dy (t )
9 2
+6 + y(t) = 2x(t)
dt dt

df (t )
with initial conditions of zero at steady state: y(0) = 0 and =0
dt t =0

3
Smith and Corripio., Principles and Practice of Automatic Process Control, Wiley, 1997, pg. 19

2-7
Solution ------------------------------------------------------------------------------------------

Taking the Laplace transform of each term in the equation yields

 d 2 y (t )   dy (t ) 
9L  2  + 6L   + L{y(t)} = 2L{x(t)}
 dt   dt 

We apply the differentiation property to obtain

9s2Y(s) + 6sY(s) + Y(s) = 2X(s)

Solving for Y(s) gives

2
Y(s) = X(s)
9 s + 6s + 1
2

Example 2.3-44. ----------------------------------------------------------------------------------

Obtain the Laplace transform of the equation c(t) = U(t − 3)[1 − e-(t - 3)/4]

Solution ------------------------------------------------------------------------------------------

Let c(t) = f(t − 3) = U(t − 3)[1 − e-(t - 3)/4] then f(t) = U(t) − U(t)e-t /4

1 1 1
L{f(t)} = F (s) = −

=
s s + 1/ 4 s (4 s + 1)

Applying the translation property gives

L{c(t)} = C(s) = L{f(t − 3)} = e-3s F (s)


e −3 s
Therefore C(s) =
s ( 4 s + 1)

We can use the final value property to check the validity of this answer

lim c(t ) lim


= U(t − 3)[1 − e-(t - 3)/4] = 1
t→∞ t→∞

lim sFˆ ( s ) lim e −3 s


= s =1 Check!
s→0 s → 0 s ( 4 s + 1)

4
Smith and Corripio., Principles and Practice of Automatic Process Control, Wiley, 1997, pg. 20

2-8

You might also like